2015
DOI: 10.5194/acp-15-10509-2015
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene (C<sub>2</sub>H<sub>2</sub>) and hydrogen cyanide (HCN) from IASI satellite observations: global distributions, validation, and comparison with model

Abstract: Abstract. We present global distributions of C 2 H 2 and hydrogen cyanide (HCN) total columns derived from the Infrared Atmospheric Sounding Interferometer (IASI) for the years 2008-2010. These distributions are obtained with a fast method allowing to retrieve C 2 H 2 abundance globally with a 5 % precision and HCN abundance in the tropical (subtropical) belt with a 10 % (25 %) precision. IASI data are compared for validation purposes with ground-based Fourier transform infrared (FTIR) spectrometer measurement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…After the Montreal Protocol has been implemented in 1989, a slowdown of the anthropogenic stratospheric depletion was observed (Strahan and Douglass, 2018). Even though O 3 recovers in the upper-and mid-stratosphere, a decline in lower stratospheric O 3 is observed by remote sensing measurements (Kyrölä et al, 2013;Nair et al, 2015;Vigouroux et al, 2015). Recently, a lower stratospheric O 3 decline of about 1.5 DU has been reported between 2001 and 2016 by Ball et al (2018, their Fig.…”
Section: The Influence Of In-cloud Ovoc Oxidation During the Indonesian Peatland Firesmentioning
confidence: 96%
See 2 more Smart Citations
“…After the Montreal Protocol has been implemented in 1989, a slowdown of the anthropogenic stratospheric depletion was observed (Strahan and Douglass, 2018). Even though O 3 recovers in the upper-and mid-stratosphere, a decline in lower stratospheric O 3 is observed by remote sensing measurements (Kyrölä et al, 2013;Nair et al, 2015;Vigouroux et al, 2015). Recently, a lower stratospheric O 3 decline of about 1.5 DU has been reported between 2001 and 2016 by Ball et al (2018, their Fig.…”
Section: The Influence Of In-cloud Ovoc Oxidation During the Indonesian Peatland Firesmentioning
confidence: 96%
“…The CO 2 line mixing in that range is accounted for as described by Duflot et al (2013). A first HRI of HCN was already set up for the IASI observations by Duflot et al (2015), but here we set up a new more sensitive one following the iterative procedure presented by Franco et al (2018).…”
Section: Appendix A: Hcn Retrievals From Iasi Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This IASI dataset may also be used in the future to study a single plume at different times to inform on the loss during transport. Further insight into the transport and chemistry may be gained by using IASI's capability to measure several fire species simultaneously, such as HCN or C 2 H 2 (e.g., Duflot et al, 2015). This would be useful for the characterization of the chemistry ongoing in a fire plume outflow.…”
Section: Discussionmentioning
confidence: 99%
“…Rosanka et al (2021a) showed that the in-cloud OVOC oxidation has a significant impact on the predicted concentrations of VOCs, key oxidants, and O 3 . In the past, global atmospheric chemistry models were not capable of representing this process explicitly or in its full complexity (Ervens, 2015). However, the recently developed Jülich Aqueous-phase Mechanism of Organic Chemistry (JAMOC, Rosanka et al, 2021a, b) comprises an advanced in-cloud OVOC oxidation scheme suitable to be used in the ECHAM/MESSy Atmospheric Chemistry (EMAC, Jöckel et al, 2010) model.…”
mentioning
confidence: 99%